Fluoroscopic-Guided Lumbar Spinal Drain Insertion for Thoracic Aortic Aneurysm Surgery. (October 2017) - Awad, Hamdy; Ramadan, Mohamed Ehab; Tili, Esmerina; Hackett, Kathryn; Bourekas, Eric C.
Abstract : We retrospectively reviewed the medical records of 11 patients who were referred by anesthesiologists to an interventional neuroradiologist for fluoroscopy-guided lumbar spinal drain insertion for thoracic aortic aneurysm repair between January 2010 and June 2015. Successful drain insertion was achieved in all patients. Three (27.3%) patients developed drain-related complications. Fluoroscopy-guided spinal drain insertion is an alternative to the conventional, nonimage-guided, blind technique used by anesthesiologists when they expect to encounter difficulty with insertion or in cases of failed insertion. Abstract : Supplemental Digital Content is available in the text.Published ahead of print December 19, 2016.